The use of crude oil light hydrocarbon fractions as scintillators in radioactive counting - Cavado, A.; Mora, N.; Fuentes, M.; Ríos, L.; Navarro, A.; Pérez, J.; Jáuregui, F.; Desdín, L. (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Véase archivo PDF